Thiazolidine derivatives as potent and selective inhibitors of the PIM kinase family. - Bataille, C; Brennan, M; Byrne, S; Davies, S; Durbin, M; Fedorov, O; Huber, K; Jones, A; Knapp, S; Liu, G; Nadali, A; Quevedo, C; et al. (Elsevier, 2017)
The PIM family of serine/threonine kinases have become an attractive target for anti-cancer drug development, particularly for certain hematological malignancies. Here, we describe the discovery of a series of inhibitors of the PIM kinase family using a high throughput screening strategy. Through a combination of molecular modeling and optimization studies, the intrinsic potencies and molecular properties of this series of compounds was significantly improved. An excellent pan-PIM isoform inhibition profile was observed across the series, while optimized examples show good selectivity over other kinases. Two PIM-expressing leukemic cancer cell lines, MV4-11 and K562, were employed to evaluate the in vitro anti-proliferative effects of selected inhibitors. Encouraging activities were observed for many examples, with the best example (44) giving an IC50 of 0.75μM against the K562 cell line. These data provide a promising starting point for further development of this series as a new cancer therapy through PIM kinase inhibition.